2015
DOI: 10.3892/etm.2015.2950
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide improves neural function in rats following cardiopulmonary resuscitation

Abstract: Abstract. The alleviation of brain injury is a key issue following cardiopulmonary resuscitation (CPR). Hydrogen sulfide (H 2 S) is hypothesized to be involved in the pathophysiological process of ischemia-reperfusion injury, and exerts a protective effect on neurons. The aim of the present study was to investigate the effects of H 2 S on neural functions following cardiac arrest (CA) in rats. A total of 60 rats were allocated at random into three groups. CA was induced to establish the model and CPR was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Although CA can lead to ischemia/reperfusion (I/R) injury in every organ in the body, it is especially detrimental to the brain and the heart. The principal pathological cause of organ damage is excessive apoptosis and autophagy (4,5), the extent of which has been found to correlate with poor neurological prognosis (6)(7)(8). A number of studies have demonstrated that hypothermia can attenuate neurological damage following I/R injury by reducing neural apoptosis and preventing autophagy overactivation (4,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Although CA can lead to ischemia/reperfusion (I/R) injury in every organ in the body, it is especially detrimental to the brain and the heart. The principal pathological cause of organ damage is excessive apoptosis and autophagy (4,5), the extent of which has been found to correlate with poor neurological prognosis (6)(7)(8). A number of studies have demonstrated that hypothermia can attenuate neurological damage following I/R injury by reducing neural apoptosis and preventing autophagy overactivation (4,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the levels of MDA, NO, and hydrogen peroxide were significantly elevated by OGD insults, and subsequently inhibited by NaHS treatment as well. Recent studies have shown that ROS have multiple biological functions other than directly damaging brain cells during I/R injury, such as activating the HIF-1 pathway which is critical to the IPC ( Wang et al, 2015 ; Lin et al, 2016 ). In aged brain cells, these ROS-induced protective signaling pathway can be activated transcriptionally, but are eventually inhibited ( Signorini et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is commonly caused by either interrupted or reduced blood supply to the brain such as ischemia, thereby leaving brain cells in a oxygen-glucose deprivation (OGD) condition. Even a short term of OGD can cause irreversibe damages to brain cells, while subsequent reperfusion, restoring blood supply to the brain, may aggravate the damage even further ( Lin et al, 2016 ). Ischemia/reperfusion (I/R) induced oxidative stress, caused by impaired metabolism in the brain cells, is believed to be the one of the major contributors to brain I/R injury ( Zeiger et al, 2009 ; Ma et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The rats in Inhibition group were intravenously injected with 1 mL sterile diluted hydroxylamine (an inhibitor for H2S, CAS 7803-49-8, Sigma) at a dose of 40 μmoL/kg·d at 1 h after ROSC. The doses of NaHS and hydroxylamine were chosen based on our previous study and other references [19] [20] [21]. The rats in Control group received 1 mL sterile saline at 1 h after ROSC.…”
Section: Methodsmentioning
confidence: 99%